Flexoelectricity in nematic domain walls. - Elston, S (2008)
Flexoelectric effects are studied in the domain walls of a nematic liquid crystal device showing the Freedericksz transition. Walls parallel to the alignment direction have a strong twist distortion and an electro-optic effect dominated by e1-e3 is seen. Walls perpendicular to the alignment direction have a strong splay-bend distortion and an electro-optic effect dominated by e1+e3 is seen. This allows the study of both flexoelectric coefficient combinations in a single device.